AGE-RELATED CHANGES OF HEMORHEOLOGICAL STATUS - E. E. Bitkova; K. K. Ilyashenko; V. B. Khvatov; A. Yu. Simonova (Неотложная медицинская помощь, 2016)
ABSTRACT. The paper presents the results of hemorheological parameters and coagulation study in 67 volunteers of three age groups, including young, middle-aged and elderly people. Studies have shown that values of the vast number of blood rheological parameters increase with advancing age, which is mostly significant after 60 years. Based on the findings, it is concluded that the presented results of hemorheological parameters studies in patients older than 60 years should be used as a comparison group in evaluation of the disease severity and the effectiveness of treatment for geriatric patients.